La logica dell’inconscio: Matte Blanco e il cinema di Resnais - Sili, Gioia (B@belonline, 2022)
Within the relationship between cinema and psychoanalysis, the figure of Ignacio Mate Blanco offers an original interpretation. In this regard, the Chilean psychoanalyst’s thought appears fruitful not so much in the direction of a rigid application of categories to specific films, but rather as a precious starting point for a reflection on images. In this perspective, the paper aims to make the concept of Matte Blanco’s psychoanalysis resonate in the Alain Resnais’s cinema, seeing in the open theory a frame of reference within which to propose readings of particular works.